The Potential of Various Composting Materials and Biochar as Soil Amendments to Increase Soil Nitrogen Availability (A Review) - Raidasari, Fatharani; Sofyan, Emma Trinurani (Jurnal Online Pertanian Tropik, 2025)
Nitrogen is an essential soil nutrient that is often a limiting factor in agricultural practices due to its tendency to be easily lost from the soil through various natural processes. Maintaining and increasing nitrogen availability in the soil is a primary focus in efforts to increase agricultural productivity. The purpose of this article is to provide information on the potential of various compost and biochar materials as soil amendments. The method used was a literature review to collect data related to compost and biochar. Various sources of compost and biochar contain varying nutrient contents, which have the potential to increase nitrogen availability in the soil. Compost application to the soil contributes to the nitrogen cycle through mineralization and immobilization processes, and nitrogen adsorption by biochar can reduce nitrogen leaching. The application of various types of compost or a combination with biochar is recommended to maintain nutrient balance and improve soil quality. Future research can explore further to determine optimal strategies for compost and biochar application to support more productive and sustainable agriculture.